Does real earnings management have an influence on firm value with moderation from tax avoidance? - Nugraha, Meilisa Tri; Wibowo, Jevennie; Firmansyah, Amrie; Trisnawati, Estralita (Educoretax, 2025)
Various ways are done by the company to boost the value of the business in order to display positive financial performance results for investors. Real earnings management and tax avoidance are efforts to increase the value of companies that are considered legal to do. This study aims to examine whether real earnings management has an effect on firm value with the role of tax avoidance as moderation, and ROA and DAR as control variables. The data used in this study are consumption sector companies, food and beverage industry sub-sectors listed on the Indonesia Stock Exchange (IDX) with an observation period of 2020-2022 sourced from www.idx.co.id and the entity's official website. Purposive sampling is used to collect panel data, which is the form of data used in the quantitative research approach.The results of the data obtained amounted to 60 samples tested assuming data analysis in determining the best model as the basis for research in the form of the Lagrange Multiplier test, Chow test, and Hausman test. The results of the research obtained show that real earnings management has a positive effect on firm value with tax avoidance that does not moderate to strengthen this influence. This study uses tax avoidance as a moderation variable that can be developed in future research to increase literacy related to the influence on firm value.